Pengaruh Risiko Kredit Dan Risiko Likuiditas Terhadap Profitabilitas Pada Bank BUMN - Ivan Krisna Aji; Gusganda Suria Manda (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
Banks in carrying out their operations are certainly not free from various kinds of risks. Bank business risk is the uncertainty regarding an outcome that is expected or expected to be received. Non Performing Loan (NPL) Is a financial ratio related to credit risk. Loan to Deposit Ratio (LDR) is a ratio that measures a Bank's ability to meet its obligations. This study aims to determine the effect of credit risk (NPL), liquidity risk (LDR) partially and simultaneously on profitability as indicated by the ROA (Return to Assets) ratio using multiple linear regression tests for state-owned banks listed on the Indonesia Stock Exchange for the period 2015- 2019. This type of research is descriptive research with secondary data derived from the financial statements of listed BUMN banks and obtained directly from the website on the Indonesia Stock Exchange. This study uses data from 2015-2019 with a sample size of 4 Bumn Banks from a total population of 20 Bumn Banks. The results of this study indicate that; 1) Credit Risk (NPL) simultaneously affects profitability partially; 2) Partially liquidity risk (LDR) has no effect on profitability; and 3) Credit Risk and Liquidity Risk simultaneously affect profitability.